Effect of Energy Restriction on Malondialdehyde Levels in Rats - Andi millaty Halifah Dirgahayu; Aminuddin Aminuddin; Arif Santoso; Nurpudji Astuti; Ika Yustisia; Irfan Idris (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
Elevated malondialdehyde (MDA) levels indicate the occurrence of cell membrane oxidation. Calorie restriction is known to extend life expectancy. This study aims to investigate the effect of calorie restriction on MDA levels in young and old rats. An experimental approach was employed using Rattus norvegicus Wistar strain as the experimental animals, with a pre-post-test control group design. A total of 28 white rats were included in this study and were divided into four groups. The control groups, Group A and Group B, received standard feed and unrestricted access to distilled water, while the treatment groups, Group C and Group D, were fed with a 40% reduction in calorie intake and distilled water. Data analysis was performed using SPSS 21.0 (SPSS, Inc., Chicago, IL) with a 0.05 significance level. The results showed a difference in MDA level changes between group B (control group) and group D (treatment group) (p<0.05). This study concludes that MDA levels are higher in the elderly compared to young rats, and a 40% calorie restriction can reduce MDA levels.